Exploring the interactions between radiation therapists and cancer patients : an ethnographic study - Merchant, Susan Patricia (Curtin University, 2011)
Radiation therapists are responsible for the planning and delivery of radiation therapy treatment for patients diagnosed with cancer as prescribed by radiation oncologists. Treatment courses with a curative intent usually involve daily interaction between radiation therapists and the patient for six to eight weeks. Evidence in the literature suggests that patients with a diagnosis of cancer can experience levels of anxiety and depression, and radiation therapy can also invoke fear and anxiety. Psychosocial support of the patient has been found to enhance the treatment experience and the efficacy of the treatment. Radiation therapists need to communicate with patients and may have a role to play in reducing patient anxiety and distress. The aims of this study were to gain an understanding of the underlying beliefs, values, practices and systems that form the current culture of radiation therapists and how it might be affecting the extent of supportive care that their patients receive.An ethnographic approach enabled the gathering of rich descriptive data through observations and interviews conducted in two radiation therapy centres between May-November 2009. Participants were radiation therapists, patients, nurses and administration staff. Four group interviews with radiation therapists were conducted between April-June 2010. Data was analysed by familiarisation with the raw data, charting themes using coding and identifying subthemes, and interpretation using mind mapping diagrams, consultation with supervisors and presentations to peers. Extensive reflective journaling was also used to assist data analysis.Radiation therapists’ interactions with patients are complicated by a combination of radiation therapists’ cultural aspects, radiation therapists’ perceptions of supportive patient care, and the environment where the interactions occur. This study disclosed new understandings and highlighted the complexities of four main cultural concepts. These concepts consist of: a disease focus, technology motivated, task and teamwork behaviour and a heightened awareness of time and space.Interactions between radiation therapists and patients were identified as (a) structured consisting of information provision and instruction giving, and (b) unstructured (i.e. informal talk). The findings of the study indicated the lack of appropriate space or available space within treatment areas restricted radiation therapists interacting in-depth or in meaningful interactions with patients. The amounts of time radiation therapists had available for interactions were limited because their role within the treatment area required greater amounts of time undertaking technical tasks. There was also pressure to keep to time with an emphasis on efficient throughput of patients. However, patients found interacting with radiation therapists helpful in reducing anxiety and normalising the process but required information to be individualised to cater for individual needs.This study provides an understanding of the cultural and environmental factors underpinning the radiation therapist/ patient relationship. The findings suggest the need for Australian radiation therapists’ to reassess their current approaches to supportive patient care. This study highlighted the need for radiation therapy education and training to be inclusive of communication skills and their use within different clinical spaces. The findings of the study suggest the need to develop a structured approach to supportive patient care by radiation therapists and to the future professional role development of radiation therapists in supportive patient care.